(untitled) (Medico Legal Update, 2021)
Gene therapy has proven its potential in treatment of several human diseases. Most recent method in a long line of the genome-editing-techniques is called “A Clustered-Regularly-Interspaced-Short-PalindromicRepeat-associated-protein9” abbreviated as CRISPR-Cas9. The scientists and researcher have long sought to the control, and modification the DNA that consider “the code of life”. The CRISPR-Cas9technology is offer very important improvements that differ about other gene-editing.technologies, it’s uncomplicated to apply & low-cost, also have comparatively high degree of the efficiency and precision . This technology uses a “.ribonucleic acid.(RNA)-guided. Deoxyribonucleic. acid-DNA-endonuclease.”, Cas9, which induces double-strand breaks (DSBs) in the target site, the DSBs was repaired by the use of a variety of cellular DNA-repair systems leading to changes in target sites, that technology have proven to be effective to investigation, prevention, and treatment of diseases. This review summarizes contemporary evolution in CRISPR –Cas9 system technology and their uses in treatment of common diseases.